Comprehensive steroid profiling by liquid chromatography coupled to high resolution mass spectrometry. Issue 183 (October 2018) - Kaabia, Zied; Laparre, Jérôme; Cesbron, Nora; Le Bizec, Bruno; Dervilly-Pinel, Gaud
Graphical abstract: Highlights: A steroidomics workflow to monitor n >150 steroids in urine has been developed. UHPLC-HRMS/MS simultaneous analysis of free/conjugated C18, C19 and C21 steroids. Homemade steroids database (n >150) available. Workflow enables investigating large steroid profile disruptions. Workflow successfully applied to boldenone metabolites detection in bovine urine. Abstract: A steroidomics workflow has been developed in the objective of monitoring a wide range (n >150) of steroids in urine. The proposed workflow relies on the optimization of an adequate SPE extraction step followed by an UHPLC-HRMS/MS simultaneous analysis of both free and conjugated forms of C18, C19 and C21 steroid hormones. On the basis of 44 selected steroids, representative of main classes of steroids constituting the steroidome, the performances of the developed workflow were evaluated in terms of selectivity, repeatability (< 13%) and linearity (R2> 0.985 in the concentration range [0.01–10 ng/mL]). As metabolites identification and characterization constitute the bottleneck of such profiling approaches, a homemade database was created encompassing a large number of characterized free and conjugated steroids (n> 150) for putative steroid-like biomarkers identification purposes. The efficiency of the workflow in highlighting fine modifications within the urinary steroidome was assessed in the frame of an anabolic treatment involving an intra-muscular administration of boldenone undecylenate (2 mg/kg) to veals (n=6) and the investigation of potential steroid biomarkers. Besides monitoring known phase II metabolites of boldenone in the bovine specie, namely, boldenone glucuronide and sulfate, the applied strategy also permitted to observe, upon boldenone administration, a modified profile of epiboldenone glucuronide. Furthermore, 31 signals corresponding to non-identified steroid species could also be highlighted as impacted upon the exogenous steroid treatment. This study is the first to simultaneously investigate both free and conjugated C18, C19 and C21 steroid hormones in their native form using UHPLC-HRMS/MS and allowing their comprehensive profiling. This strategy was probed in-vivo.